Gut microbiota variability in dung beetles: prokaryotes vary according to the phylogeny of the host species while fungi vary according to the diet - Natta, Gianluca; Voyron, Samuele; Lumini, Erica; Laini, Alex; Roggero, Angela; Fiorito, Alessandro; Palestrini, Claudia; Rolando, Antonio (Frontiers in Insect Science, 2025)
Dung beetles (Coleoptera, Scarabaeoidea) support several ecological processes and services making them important ecosystem engineers. The dung beetle gut microbiota is involved in many of these ecological services. In the present study, we analyzed the microbiota of 90 individuals of three Onthophagus species feeding on different dung types. Our aim was to understand whether the species identity affected the microbiota more than the dung ingested and whether this conditioning applied equally to prokaryotes and fungi. We also compared the taxonomic and functional variability of the microorganisms to check for similarities between individuals. Using molecular analyses, we characterized the alpha and beta diversities, core and indicator taxa and taxonomic and functional composition of the gut microbiota. Alpha diversity analyses revealed diet, species and sex to influence diversity parameters but no clear differences in the diversity patterns for prokaryotes vs fungi. Conversely, all other analyses consistently showed differences in the composition patterns for prokaryotes vs fungi, with prokaryotes mostly varying according to host species identity and fungi varying according to dung type. This suggests that most prokaryotes in the dung beetle microbiota are definitive symbionts, whereas many fungi are transient symbionts. We found evidence of great similarity in the functional composition of the microbiota despite strong taxonomic dissimilarities. The results emphasize the need to consider both the prokaryotic and fungal components of the microbiota. They also suggest microbial composition analyses to be preferable to alpha diversity analyses for identifying patterns of variation that depend on phylogeny and diet.